Insight into aphid mediated Potato Virus Y transmission: A molecular to bioinformatics prospective - Bhoi, Tanmaya Kumar; Samal, Ipsita; Majhi, Prasanta Kumar; Komal, J.; Mahanta, Deepak Kumar; Pradhan, Asit Kumar; Saini, Varun; Nikhil Raj, M.; Ahmad, Mohammad Abbas; Behera, Partha Pratim; Ashwini, Mangali (Frontiers in Microbiology, 2022)
Potato, world's most popular non-grain crop reported to provide food source for nearly a billion people. It is prone to a number of biotic stressors that affect yield and quality, out of which Potato virus Y (PVY) occupies the top most position. Experimentally, PVY can be transmitted mechanically and by sap-feeding aphid vectors. As application of insecticide causes increase in resistant vector population as well as cause detrimental effect on environment, genetic resistance and the vector-virus control are the two core components for controlling the deadly PVY. Through using transcriptomic tools global differential gene expression and gene discovery, several loci and genes associated with PVY-resistance have been widely identified. To increase our understanding on molecular response of PVY on the host potato plant as well as on the vector aphid the knowledge of genome organization and protein, function of PVY encoded protein, genetic diversity, molecular aspects of PVY transmission by aphids, transcriptome profiling of PVY infected Potato cultivars is highly necessary. There are several techniques like molecular and bioinformatics tools which identify and monitor virus transmission. Several studies have conducted to understand the molecular basis of PVY resistance/susceptibility interactions and their impact on PVY epidemiology by studying the interactions between the virus, its vector, and the host plant. This review will present the current knowledge of PVY transmission, epidemiology, genome organization, molecular to bioinformatics responses and its management in an effective way. Keywords: Potato, Potato virus Y (PVY), vector, virus, molecular, bioinformatics, transcriptome, genome, aphid